Digital Innovation and Higher Education Quality: An Interdisciplinary Integration-Driven Model - LiPeng, Wang; Wai Yie, Leong; Dou, Wen (INTI International University, 2025)
Digital transformation profoundly impacts higher education through increased quality and integration between disciplines, but its its specific mechanisms, particularly the role of interdisciplinary integration in mediating digital innovation and educational quality, remain underexplored. In developing a theoretical model for explaining how digital innovation raises educational quality, this study employs a mixed-methods approach combining literature review, survey, and in-depth interviews with university students and instructors. It concludes that digital innovation maximizes resource utilization, enhances instructional efficiency, promotes equitable knowledge dissemination, and strengthens innovation capacities. Integration between disciplines strengthens the impact of digital innovation, generating a positive feedback loop that continues to enhance educational quality. This work enriches theoretical and practical insights into digital education and integration between disciplines and can serve as a guideline for universities to promote digital and integration instruction. It can also inform policymakers in supporting educational digital transformation. There is a potential for future studies to expand data collection in universities worldwide and explore new technology such as AI, big data, and blockchain in driving smarter and fairer higher education. These findings offer actionable strategies for institutions to bridge resource gaps and foster equitable digital transformation.